2005
DOI: 10.1029/2004jb003251
|View full text |Cite
|
Sign up to set email alerts
|

Neotectonic architecture of Taiwan and its implications for future large earthquakes

Abstract: [1] The disastrous effects of the 1999 Chi-Chi earthquake in Taiwan demonstrated an urgent need for better knowledge of the island's potential earthquake sources. Toward this end, we have prepared a neotectonic map of Taiwan. The map and related cross sections are based upon structural and geomorphic expression of active faults and folds both in the field and on shaded relief maps prepared from a 40-m resolution digital elevation model, augmented by geodetic and seismologic data. The active tandem suturing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
345
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(359 citation statements)
references
References 67 publications
(140 reference statements)
14
345
0
Order By: Relevance
“…Chen et al (2008) suggested that there are two faults delineated by seismicity distribution with backthrust and strike-slip faulting mechanisms. The right-lateral Meishan strike-slip fault, located at the northern margin of our study region, acts as a tearing fault (Shyu et al, 2005). According to our results for the focal mechanisms and hypocentral depths shown in Figure 8, the west-dipping trend of the fault is consistent with a dominant backthrust.…”
Section: Discussionsupporting
confidence: 64%
“…Chen et al (2008) suggested that there are two faults delineated by seismicity distribution with backthrust and strike-slip faulting mechanisms. The right-lateral Meishan strike-slip fault, located at the northern margin of our study region, acts as a tearing fault (Shyu et al, 2005). According to our results for the focal mechanisms and hypocentral depths shown in Figure 8, the west-dipping trend of the fault is consistent with a dominant backthrust.…”
Section: Discussionsupporting
confidence: 64%
“…Presently, rapid crustal movement and widely distributed active structures are the geological characteristics of this young tectonic entity (Yu et al 1997(Yu et al , 1999Chang et al 1998). Hence, in terms of tectonic activity, seven and four neotectonic domains, respectively, can be identified in western and eastern Taiwan, and what's more, each domain is bound by its own distinct active structure (Shyu et al 2005). Beyond this, each may have its own response to stress accumulation and faulting.…”
Section: Discussionmentioning
confidence: 99%
“…5). The western margin of the HUAL block is defined following the eastern margin of the Central Range, which corresponds to a geologically suspected fault, the Central Range Fault (Biq 1965;Lu and Hsu 1992;Shyu et al 2005). A recent study on local seismicity (Chen et al 2012) suggested a seismically active structure along the edge of the Central Range in the Hualian City area.…”
Section: Block Rotation Modelingmentioning
confidence: 99%